PENINGKATAN DIGESTIBILITAS DAN PERUBAHAN STRUKTUR TANDAN KOSONG KELAPA SAWIT OLEH PRETREATMENT Pleurotus floridanus DAN ASAM FOSFAT - , Isroi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Oil palm empty fruit bunches (OPEFB) is abundance and not optimally utilized as lignocellulose-based products. OPEFB has low digestibility and difficult to process into its derivatives. This study aims to improve digestibility of OPEFB through biological pretreatment with white-rot fungi. Stages of this study were (1) selection white-rot fungi which selectively degrade lignin, (2) enhancement the digestibility of OPEFB by Mn2+ and Cu2+ addition, (3) improvement digestibility of OPEFB by a combination of biological pretreatment with phosphoric acid pretreatment. All the studies were conducted on laboratory scale. Observations were made on the changes of dry weight, lignin, cellulose, hemicellulose, physical structure by SEM analysis, functional groups by FTIR analysis, and the crystallinity of cellulose. Screening is done on Polyota sp, Pleurotus sp and sp Agraily. Pleurotus sp chosen for further experiments and identified as P. Floridanus LIPIMC966, because it can alter the lignin content from 19.63% to 15.22%, hemicellulose from 14.77% to 12.63%, and increase cellulose from 39.92% to 56.04%. The addition effect of Mn2+ and Cu2+ on the biological pretreatment using P. Floridanus could reduces the dry weight from 27.43% to 32.88%